Value Education: The Need of the Hour? An Assessment of Education Philosophy of Swami Vivekanand and Mahatma Gandhi: Exploring the Philosophy of Swami Vivekanand and Mahatma Gandhi for Addressing the Crisis of Value Education in Colonial Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Indians have inherited a colonial educational structure which is based on western values and somehow seems to have lost its Indianess. Hence, it has managed to create a generations of men and women who are relentlessly pursuing the rapacious lifestyle in search of happiness and peace, which they are unable to find. This has led to increasing number of cases of depression and even suicides. The West today is turning towards East in search for answers in the spiritual and philosophical traditions. The philosophy of great personalities like Swami Vivekanand and Mahatma Gandhi and especially their views on education are extremely relevant than they ever were. This paper is an attempt to look at the philosophy of these two great personalities in search for answers.